Analysis of Religius Character of Islamic Full Day School Students - Pura, Khusnia Indra; Maliana, Aprilia Dita; Ilmi, Dian Shafira; Rahma, Nazila Aulia; Febriyanti, Novi sinta; Setiyawati, Enik (Procedia of Social Sciences and Humanities, 2024)
This research aims to determine the analysis of the religious character of Islamic-based full day school elementary school students at SD Muhammadiyah 2 Tulangan. This research uses a field research method with a qualitative approach. The research carried out three stages when collecting data, namely observation from the results of observations carried out, collecting school data obtained from interviews with one of the teachers and also interviews conducted with the principal at the elementary school. . The research was conducted on 29 April 2024 - 03 May 2024. SD Muhammadiyah 2 Tulangan has a superior program that supports students' religious character in accordance with the school's vision and mission. Implementation of the school's vision and mission with various activities. The school gives appreciation to students who have become tahfidz of the Qur'an juz 30. The cultivation of religious character in students has been implemented since grade 1 and will continue to be developed until grade 6. Various activities are carried out by the school to instill religious character in students. In cultivating a religious character, of course there are supporting and inhibiting factors and factors that influence internally and externally.